INDEPENDENT CURRICULUM: IMPLEMENTATION OF SOCIAL SCIENCE AND ARTS AND CULTURE LEARNING THROUGH P5 AT SMA NEGERI 10 PONTIANAK - Iwan Ramadhan (Jurnal Scientia, 2023)
The purpose of this study was to determine the implementation of the independent curriculum in intracurricular learning and the project to strengthen the Pancasila student profile. Teachers and educators at SMA Negeri 10 still need understanding in understanding and applying the dimensions of the Pancasila student profile (P5) in phase E (grade X). The problems faced by SMA Negeri 10 Pontianak include educators still needing an understanding of Learning Outcomes (CP) and the five dimensions of the Pancasila profile (P5) so that the implementation of the independent curriculum produces competent student outcomes in dealing with change and in accordance with the Pancasila character. The efforts of schools and educators in solving these problems are upgrading knowledge and experience obtained face-to-face and virtually. The method used is descriptive qualitative type, through data collection techniques of observation, interviews and documentation. The findings of this study are that teachers need understanding in analyzing the difficulties and needs of each student to implement an independent curriculum that refers to Learning Outcomes (CP) and the five dimensions of the Pancasila profile (P5). This is because SMA Negeri 10 has limited time which is divided into two learning session schedules. Then the P5 activities have not been maximally implemented because the school building is still under construction. So that P5 activities cannot be optimal. Finally, skills and honing soft skills are carried out through direct training or through devices (internet) such as Zoom, YouTube, etc.